PROGRAM âLOMBOK RAWITâSEBAGAI SARANA TERAPI BAGI ANAK TUNA LARAS - Verrysaputro, Exwan Andriyan; Ardhiantoro, Akhmad RivaÃ¢Â€Â™i (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2014)
Student Creativity Program(PKM) of "Lombok Rawit" (Latihan Among Bekso dan Karawitan) is motivated by a will to make traditional Javanese gamelan music and dance as a means of therapy for Mentally Handicapped students. Through this program, Mentally Handicapped children are expected to be familiar with the culture Javanese, while getting a therapy to reduce emotional and behavioral deviations. PKM is applied to Mentally Handicapped children in Special school (SLB) âEâPrayuwana Yogyakarta. The number of students in special schools was 25 people. Training was conducted in April-July 2014, the results were achieved after the training, namely: (1) the increasing of the value of the post-test by 68%. This percentage is obtained from the tabulated results from the instrument, which showed a reduction in the number of occurrences Mentally Handicapped children characteristics such as hyperactivity, fear, antisocial, and others. (2) The PKM team managed to hold a simple form of collaboration performances of gamelan and dance Mentally Handicapped children. (3) The PKM team managed to compile teaching materials in the form of modules and CD gamelan and dance lessons for children with the barrel so that it can be used widely by teachers and therapists of Mentally Handicapped children. Based ont he results of the PKM, it can be concluded that the training"Rawit Lombok", can be used as a therapeutic tool for Mentally Handicapped children. Based on the effectiveness of thisprogram, a team of the PKM trying to do a follow up in the form of mentoring and socialization, so that a similar program can be applied to Mentally Handicapped children in others special school.Keywords: mentally handicapped children, therapy, Lombok Rawit